FRESH FISH LANDING IN THE IQUITOS CITY, LORETO REGION - PERUVIAN AMAZON - GARCÍA-VÁSQUEZ, Aurea (2012)
This study presents the analysis of the information of the in the main ports of the city of fresh fish landingIquitos, in the years from 2008 to 2012. Landing is composed by 79% of fresh fish using a system of isothermal boxes that are transported in the cargo and passenger vessels. The commercial fishing fleets provide only 21% of total landings at fresh state. The Ucayali basin was the most important fishing area during the study period, with an average of 63.3% of the landings, followed by the Amazon basin with 31.5%. The formal vessels categorized from 6 to 8 tons are the most representative in the commercial fishing fleet.